The efficacy of adebrelimab compared with durvalumab and atezolizumab in untreated extensive-stage small-cell lung cancer: a survival analysis of reconstructed patient-level data - Wang, Bi-Cheng; Fu, Chen; Lin, Guo-He (Frontiers in Immunology, 2023)
Background: Adebrelimab showed excellent efficacy in the first-line treatment for extensive-stage small-cell lung cancer (ES-SCLC). However, whether adebrelimab is superior to durvalumab and atezolizumab remains unclear. Therefore, we, in this study, aimed to compare the survival data of adebrelimab (CAPSTONE-1 trial) with durvalumab (CASPIAN trial) and atezolizumab (IMpower133 trial) in the first-line setting of ES-SCLC patients. Methods: Online databases, including PubMed, Embase, Web of Science, and Cochrane CENTRAL, were systematically searched on December 2, 2022. The metaSurvival and IPDfromKM methods were used to analyze the summary survival curves and the reconstructed patient-level data. The main endpoints were median overall survival (OS) and progression-free survival (PFS). Results: In this analysis, survival data in the CASPIAN, IMpower133, and CAPSTONE-1 trials were collected from five published studies. The pooled median OS and PFS were 14.0 months (95% CI 11.2-16.6) and 5.6 months (95% CI 4.7-6.7) when ES-SCLC patients received chemotherapy (etoposide and cisplatin/carboplatin) and anti-PD-L1 therapy. Based on the reconstructed patient-level data, adebrelimab significantly prolonged survival outcomes against atezolizumab (OS: Hazard ratio [HR]0.76, 95% CI 0.60-0.95; PFS: HR 0.67, 95% CI 0.54-0.83) and durvalumab (OS: HR 0.75, 95% CI 0.60-0.92). Conclusion: For previously untreated ES-SCLC patients, longer survival time might be benefited from adding adebrelimab to etoposide-platinum chemotherapy. In future studies, further real-world evidence or head-to-head clinical trials are warranted to confirm the differences between the PD-L1 inhibitors.